(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Custodial violence represents one of the gravest violations of human rights, striking at the core of human dignity, personal liberty, and the rule of law. Despite the existence of comprehensive international human rights standards prohibiting torture and cruel, inhuman, or degrading treatment, custodial abuse continues to persist across South Asian jurisdictions. This article undertakes a comparative study of custodial violence in India and selects South Asian countries, namely Pakistan, Bangladesh, Nepal, and Sri Lanka, through the lens of international human rights obligations. It examines the extent to which global norms enshrined in instruments such as the Universal Declaration of Human Rights, the International Covenant on Civil and Political Rights, the Convention Against Torture, and the United Nations Standard Minimum Rules for the Treatment of Prisoners (Nelson Mandela Rules) have been incorporated into domestic legal frameworks and institutional practices. The study critically analyses constitutional safeguards, statutory provisions, judicial interventions, and accountability mechanisms governing custodial conduct in these jurisdictions. It highlights significant gaps between normative commitments and practical enforcement, underscoring challenges such as weak institutional oversight, political interference, limited access to justice, and entrenched cultures of impunity within law enforcement agencies. By adopting a comparative and human-rights-based approach, the article identifies best practices and structural deficiencies in the region’s response to custodial violence. The study concludes that effective prevention of custodial abuse requires not only legal reform but also sustained institutional accountability, independent monitoring, and adherence to international human rights standards to ensure meaningful protection of detainees’ rights in South Asia.